Evaluation and Follow-Up of the Juz ‘Amma Tahfidz Program at MI Al Wathoniyah Rejotangan - Al Azizi, Muhammad Fauzi; Kholis, Nur (Journal of Educational Research and Practice, 2024)
Evaluation is a very important thing in a curriculum. Evaluation is an ongoing series in the curriculum. Many educational institutions only evaluate the curriculum as an administrative obligation. In fact, evaluation should be more than just an administrative obligation, but rather a procedure that must be carried out for improvement and development steps. This research aims to analyze the implementation and evaluation process of the tahfidz juz 'amma program at MI Al Wathoniyah Tegalrejo Rejotangan. The research method uses qualitative research methods by collecting data by observation and interviews. The data analysis techniques involve data reduction, data presentation and drawing conclusions. The findings in the field stated that the evaluation of the tahfidz juz 'amma program at MI Al Wathoniyah Tegalrejo Rejotangan had been carried out properly and correctly. The evaluation process uses a humanistic approach and the model used is a multivariate mixture. It doesn't just stop at evaluation, the tahfidz juz 'amma program at MI Al Wathoniyah Tegalrejo Rejotangan also follows up on the evaluation results. In this follow-up process, MI Al Wathoniyah applies consistent principles in its implementation.